I slay, okay how mediated race in Western pop music videos affect a Filipina's self-concept - De Leon, Angelica Linda Leonila A. 1997-
This thesis examines the effects of mediated race on morena Filipinas. Specifically, it looks at how Beyonce affects the self-concept of her morena Filipina fans, thus posing the question: how does the representation of Beyonce's body in her album Lemonade affect and represent the self-concept of her morena Filipina fans? The researcher believes that representations of Beyonce's body have the capacity to influence the ideal image of a person's self-concept, which is why the researcher wants to determine whether its effects lead to a congruent or incongruent self-actualization. Using Carl Rogers' three components of the Self-Concept Theory, supplemented by the Representation Theory, Self-Objectification Theory and the Critical Race Theory, the thesis utilizes a thematic analysis on ten screenshots from Beyonce's Lemonade, and the fifteen online interviews with 18-25 year old members of the Beyonce Philippine Facebook group. The interviews are structured into three parts in order to discover each participant's self-image, idealized self, and perceived self-esteem. Furthermore, the study intends to take a critical look at the findings with some postcolonial analysis.